Scaling Effects for Compression Loaded of Corrugated-core Sandwich Panels - M. R. M., Rejab; N. Z. M., Zaid; J. P., Siregar; Bachtiar, Dandi (Trans Tech Publications, Switzerland, 2016)
The compressive responses and failure investigations of corrugated-core sandwich panels subjected to literal compression are presented. The results of finite element (FE) analysis using Abagus are compared with experimental results from tests on sandwich panels based on corrugations of aluminum alloy, glass fibre-reinforced plastic (GFRP) and carbon fibre-reinforced plastic (CFRP). Particular focus is placed on identifying the scaling effects of number of unit cells and the thickness of the cell walls in dominating the overall deformation and local collapse of the panel.